Arbitration as a mechanism to resolve Islamic banking disputes in Malaysia: challenges and drawbacks - Labanie, Mohamad Fateh (UUM College of Law, Government and International Studies, 2019)
Malaysia has shown tremendous progress in the Islamic Banking and Finance Industry and has become an Islamic financial hub. The comprehensive legal framework consists of legislation and dispute resolution mechanisms as crucial elements to ensure the robust development of this industry. The court system and arbitration are two significant forums to settle Islamic banking disputes brought before them. However, the court is the preferred place to be referred to rather than the arbitration even though both play the same role. The question arises, why the arbitration is less preferred rather than the court? By using legal research methods, this article seeks to analyse the challenges and drawbacks facing the current arbitration framework in dealing with Islamic Banking disputes. This study found that the Malaysian arbitration framework is facing several challenges such as an issue on high-cost, high-formality, less-speed and also uncertainty in referring any Shariah matter to the Shariah Advisory Council. This article suggests that some improvements should be made by relevant authority as well as statutory amendments should be achieved in order to strengthen the role of arbitration in Malaysia as a complementary forum to the court in settlement of Islamic financial disputes.